SOA will kill the offshore model can SOA really impact geopolitics?. - O'Connor, Paul
I know what you're thinking : SOA hype has reached an absurd level and now someone is literally proclaiming that it will change the world - but bear with me for a minute. Anyone who has been around corporate IT for the last five years or so has seen an avalanche of development work sent offshore for two primary reasons: cheaper unit labor cost and the flat-out inabilty to find qualified American developers. Also, the mainstay system development model whereby business units built up app silos, which served to minimize reuse and increase integration complexity, demanded a way to deal with the cost of its own inefficiency.